Guidelines for contributors (2008)
PROFILE Issues in Teachers’ Professional Development This journal, led by the PROFILE research group at Universidad Nacional de Colombia, is a publication for teachers of English interested in increasing their professional expertise. Starting from the assumption that our professional knowledge is enriched by different members of our academic community, this journal is mainly concerned with promoting the publication of articles written by teacher researchers.